External crisis vulnerability in Latin America and the Caribbean - Eduardo A. Cavallo; Eduardo Fernández Arias (Inter-American Development Bank (IDB), 2023)
This paper assesses the vulnerability of Latin American and Caribbean (LAC) economies to external crises. It shows that while the average LAC economy has made significant strides to reduce vulnerability to crises to its historical minimum, there is still considerable room for improvement, compared to both advanced and non-advanced economies. When compared to other non-advanced economies, the average LAC economy displays a higher level of vulnerability, mainly due to slower improvements in portfolio composition and less accumulation of international reserves since 2000. Advanced economies have lower exposure to external risk factors and a structural resilience advantage to prevent exposure from leading to crises. This analysis highlights the need for LAC economies to focus more on enhancing their risk-mitigating strategies concerning the composition of their external portfolios and reserves accumulation, which will provide a stronger buffer against external shocks and promote overall economic resilience.
Keywords: F30; F34; G01; G15; H63; 330; External crisis; Financial crisis; External balance sheet; International reserves; Macroeconomic imbalances; External debt; Foreign direct investment; External Assets and Liabilities